ANALISIS PENGARUH SERVICESCAPE TERHADAP REVISIT INTENTION DI LA RIVIERA PANTAI INDAH KAPUK 2 - Cahyuni, Winda Evelyn (SIWAYANG Journal: Publikasi Ilmiah Bidang Pariwisata, Kebudayaan, dan Antropologi, 2023)
This study aims to analyze whether there is an influence of servicescape on revisit intention at La Riviera Pantai Indah Kapuk 2. In measuring servicescape, there are 5 dimensions, namely facility aestheticss, layout, electrical equipment, ambient conditions, and employee factors to the revisit intention variable, which have 3 indicators, namely the revisit intention, recommendation intention, and the first choice. This study uses quantitative research methods, data collection is done by distributing questionnaires distributed to 100 people who have visited La Riviera and processed using SPSS 25 data processing tools. based on the results of the coefficient of determination test, servicescape affects revisit intention with a percentage of 58.3%. In the partial T test, it is found that the dimensions of layout and ambient conditions have a positive effect, while the dimensions of facility aestheticss, electronic equipment, and ambient conditions have a negative effect. In the F test simultaneously servicescape has a positive effect on revisit intention with an F table value of 2,310 which is smaller than the F count of 26,337 so that it is stated to have a positive effect.